The Influence of the Addition of Nickel on the Structure and Mechanical Properties of Aluminium Bronze Alloy - B. S, Oluwadare; A, Adebayo; J. T, Stephen (Review of Industrial Engineering Letters, 2019)
This paper describes an investigation of the influence of the addition of Nickel on the mechanical properties of aluminium bronze alloy. The investigation began by casting the specimens in a crucible pit furnace. Sand casting was utilised and was discovered to be more effective because it is inexpensive and easy to use during the production of aluminium bronze alloy. Five different samples of the aluminium bronze alloyed with 0% to 4% nickel were added into the furnace in accordance with their melting points. Nickel has the highest melting point of 1453℃, while copper, aluminium and zinc have melting points of 1084℃, 660℃ and 419℃ respectively. The mixture was manually stirred for around 5 minutes to ensure proper mixing of the alloying materials. After casting, both tensile and hardness tests were carried out on the machined, sectioned and ground specimens. An increment was observed in the samples’ hardness as the percentage composition of nickel increased while the tensile strength initially increased and then decreased. It was also observed from the results that the tensile stress for each specimen increased with strain.